Olfactory Response of Diaphorina citri to Guava Leaves Powder - Poerwanto, Mofit Eko; Solichah, Chimayatus; Wicaksono, Danar; Ulilalbab, Azizah Ridha; Ajri, Miftahul (Universitas Gadjah Mada, 2024)
Citrus Vein Phloem Degeneration (CVPD) is transmitted by the insect vector Diaphorina citri is still a major obstacle to world citrus production. Vector handling still relies on chemical insecticides which are not environmentally friendly and less effective. This study was conducted to identify the ability of dried guava leaf extract in reducing the olfactory response of D. citri. Y-tube olfactory test was conducted to identify the repellency effect of a mixture of citrus leaf extract and guava (Psidium guajava) leaf extract at various leaf ages and in various proportions to vector and its predator (Menochilus sexmaculatus). The results showed that guava leaves had a repellent effect on D. citri, but not on M. sexmaculatus. The repellant effect was higher on young guava leaves than on medium and old ones. Red guava leaves have a highest repellant effect than white guava and non-seed guava leaves. Guava leaf extract is an alternative means to control D. citri. However, the types of compounds that function as repellants need to be studied further.